Analysis of Changes in the Bioglass Coating in the Presence of Simulated Physiological Fluids - A. Talavera-Lopez; G. Roque; A. N. Ardila Arias; M. Salazar-Hernández; J. P. Ruelas-Leyva; R. Hernandez-Soto; J. A. Hernández (International Journal of Biomaterials)
Research of new materials for bone substitutes is of the utmost importance. Bioglass (BG) is an excellent material for this necessity due to its biocompatibility with surrounding tissues once implanted. Unfortunately, these implants tend to develop cracks. Therefore, an alternative is to use a hydroxyapatite (HA) coating (BHAC) to prevent crack formation and its consequent damage restoration for better properties. The BHAC formed was analyzed using different nitric acid (HNO3) concentrations. In addition, attenuated total reflectance Fourier transform spectroscopy (ATR-FTIR), energy dispersive spectrometry (EDS), scanning electron microscopy (SEM), and X-ray diffraction (XRD) were performed on the HA coating after immersion in simulated body fluid (SBF). The BHAC was submerged in a simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) to evaluate changes in the groups of the biomaterial surface, specifically the Si–OH and P–O groups. Moreover, the variations in the Ca/P molar ratio of BHAC suggested significant changes in the BG cover when subjected to a physiological environment since HA converts into tricalcium phosphate (TCP) and dicalcium phosphate dihydrate (DCPD). Also, the presence of Si ions is modified when BHAC is immersed in SIF.